HYBRID WORK AND ITS IMPACT ON SOCIAL RELATIONSHIPS WITHIN THE WORKPLACE - Basma Rahman Ouda; Ahmed Adel Abboud (Journal of Social Science, 2026)
Objective: The research explores how hybrid work affects interpersonal relationships between employees in organizations, focusing on communication and social cohesion. Method: A descriptive-analytical methodology was used, with a questionnaire as the instrument to collect data from 85 employees in an organization that operates a hybrid work system. The survey included closed and open-ended questions to measure socialization, communication tools' efficiency, and work-life balance satisfaction. Results: Hybrid work has a dual effect: it offers greater flexibility, higher satisfaction, and better time management, but limits informal communication. On-site employees showed higher social interaction and organizational commitment, while remote employees had lower social cohesion. Digital communication tools support connectivity but cannot replace face-to-face meetings for trust and relationship development. Organizational collaboration culture was the most significant predictor of social satisfaction. Novelty: The study reveals the importance of organizational culture and digital tools in hybrid work's impact on social relationships, emphasizing the need for well-implemented communication instruments.